Marketing green buildings : guide for engineering, construction and architecture - Yudelson, Jerry (Fairmont Press ; Distributed by Taylor & Francis, 2006)
Annotation Engineers, architects and contractors seeking to expand their involvement in the green buildings market need a firm grounding in the marketing strategies and tactics which are being used most successfully in this specialized and growing field. This book is intended to serve as an effective tool for professional green building enthusiasts and advocates in presenting green design features, sustainable strategies and new products to the potential green building client. The author addresses key questions such as: How is green building marketing different from other types of professional service marketing? What tools and techniques from conventional marketing can be used to greater effect in marketing green buildings? What is the size and potential of the green buildings market? And how should a firm position itself to succeed in this growing marketplace? You'll find clear descriptions of successful strategies and approaches to marketing and selling green building-related services, as well as up-to-date information on the role of LEED® in green building projects.
Keywords: Green marketing.; Sustainable buildings -- Marketing.; Architectural services marketing.; Architects and builders -- Certification.; Construction industry.; Marketing vert.; Constructions durables -- Commercialisation.; Services d'architecture -- Marketing.; Architectes et entrepreneurs -- Attestation de compétence.; Construction -- Industrie.; TECHNOLOGY & ENGINEERING -- Construction -- General.; Architectural services marketing; Construction industry; Green marketing; Commerce.; Business & Economics.; Marketing & Sales.